Overcoming Gender Disadvantages. Social Policy Analysis of urban middle-class women in Colombia (2014)
The World Bank Report 2012 starts with this statement: “Gender equality matters in itself andit matters for development because, in today’s globalized worlds, countries that use the skillsand talents of their women would have an advantage over those which do not use it.” With theframe that suggest that gender equality matters, this paper describes some policy alternativesoriented to overcome gender disadvantages in the formal labor market incorporation of theurban middle class women in Colombia. On balance, the final recommendation suggest that itis desirable to adopt policy alternatives as Community Centers, which are programs orientedto a social redistribution of the domestic work as a way to encourage women participationin the formal labor market with the social support of the members of their own community.The problem that the social policy needs to address is the segregation of women in the formallabor market in Colombia. Although the evidence shows that the women overcome theeducational gap by showing better performance in education that their male peers, womenare still segregated of the labor market. The persistence of high rates of unemployment on thefemale population, the prevalence of the informal labor market as a women labor market, andthe presence of the payment difference between men and women with similar professionaltrainings are circumstances that sustain the segregation statement. These circumstances areinefficient for the society because an economic analysis shows that the cost of maintain the statuquo is externalized in the social security system that includes health, pension and maternityleave regimens. Therefore, the women segregation involves a market failure.This paper evaluates five policy alternatives each directed to the progress of a different causaldimension of the problem: (i) Quotas in the private market, (ii) Flexible working hours,(iii) replace the maternity leave with a family leave, (iv) Increase the Community Centers forredistributing the care work, and (v) Equal payment enforcement. The first alternative looksto increase women’s participation in the formal labor market. The second, third, and fourthalternatives constitute a package addressed at redistributing care work by reducing women’sresponsibility for reproductive work in the household with the help of husbands and the localgovernment. The fifth alternative intervenes to resolve the equal payment problem.After a four criteria evaluation that measure effectiveness, robustness and improbability inimplementation, efficiency and political acceptability or social opposition, the strongest alternativeis the fostering of Community Centers that promote a redistribution of care work. Thispolicy performs well in the assessment process because it combines gender focus with importantindirect effects: child support and human capabilities. The policy also shows a bottomup implementation process that overcomes the main adoption difficulties in the gender focusprograms and is supported by strong evidence of success in the Colombian context; this evidenceis produced by both transnational actors as a World Bank and also in local accountabilityreporters executed by local institutions like Colombian Institute of Family Welfare (ICBF).